Dietary calcium intake assessment by short food frequency questionniare in thais adults living in Chiang Mai, Thailand - Sornsuvit C. (2014)
The aims of this study were to develop and validate the short food frequency questionnaire (sFFQ) to assess calcium intake from food in Thais person for use in clinical practice or community pharmacy. Data collection was performed during November 2009 to January 2010. The sFFQ consisted of 33 item of food. The frequency of food intake in sFFQ food list was interviewed by investigator. Seven day after subject were interviewed by sFFQ, subjects were asked to fill out the Three Day Dietary Record (3DR) for 3 day. Daily calcium intake assessed by both methods was calculated by using INMUCAL software, which was developed by the Institute of Nutrition, Mahidol University. The 131 subjects who completed sFFQ and 3DR had mean age of 24.4 years, 71.3% were female. The mean daily calcium intake assessed by sFFQ and 3DR were 692.0 ± 524.9 mg and 477.4 ± 261.9 mg, respectively. The mean daily calcium intakes assessed by sFFQ were significantly higher than 3DR (p < 0.05). The Spearman's correlation coefficient between calcium intakes assessed by the two methods was 0.18 (p <0.05). In conclusion, the newly developed sFFQ was a suitable tool for the determination of calcium intakes in Thais adults. The next step in assessing the validity of this sFFQ will be its use in clinical setting such as community pharmacy or outpatient clinic. © 2011 Sornsuvit et al.